Anton Sovre in Anton Sovre - Kristan, Matic (Keria (Ljubljana), 2021)
The article describes the youth and education of Anton Sovre, who went on to become an eminent classical philologist and translator. He was born in a family of farmers in the village of Šavna Peč, where he also grew up. His father retired as an invalid after a railway accident and the family moved to the town of Krško. Sovre obtained lower secondary education in Celje and higher secondary education in Ljubljana. At first he studied at the University of Vienna, where he was also the president of Slovenija, a society of Slovene students; later on, he studied at the University of Graz. He applied for final exams in 1912, but failed to complete them in entirety. He married Albina Schöner during the First World War. He graduated as late as 1925 by taking graduation exams at the University of Ljubljana. In addition, the article summarises the lives of his seven siblings, including the military service of all of his five brothers during the First World War.
Keywords: biografije; Klasična filologija; prevajalci; slovenski klasični filologi; Sovre, Anton